2022
DOI: 10.3390/app12083736
|View full text |Cite
|
Sign up to set email alerts
|

Less Rare-Earth Electromagnetic Design for a High-Performance Permanent Magnet Motor

Abstract: This paper presents an electromagnetic design alternative using the so-called banana-shaped magnets, achieving magnet weight reduction of 21.82% for the same performance as the baseline motor in the case study. Typically, parallel magnetization is used in this topology because it provides the manufacturing advantage of not building a specific magnetizing device required to achieve radial magnetization. Therefore, as its main contribution, this paper proposes using tilted magnetization, demonstrating that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Sci. 2024,14, 4167 16 of 20 increased from 3.5 mm to 4.5 mm, maximum torque increased by up to 6.33%, while the range of maximum torque rotation decreased by up to 2.10%.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Sci. 2024,14, 4167 16 of 20 increased from 3.5 mm to 4.5 mm, maximum torque increased by up to 6.33%, while the range of maximum torque rotation decreased by up to 2.10%.…”
mentioning
confidence: 95%
“…Also, Muhammed Muhsin Coşdu et al used a multiobjective differential evolutionary optimization algorithm (MODE) on an external rotor PMSM hub motor for the "Efficiency Challenge" competition to determine its lightweight potential [13]. Christian A. Rivera et al found that the application of banana-shaped magnets can improve motor performance for the same magnet weight [14]. Keun-Young Yoon et al proposed a novel flared-ferrite IPM model as an alternative to the conventional spoke-ferrite IPM model.…”
Section: Introduction 1research Background and Motivationmentioning
confidence: 99%
“…In these high-performance applications, there are a number of benefits that can be taken into account over typical electrical machines, including greater energy density, superior torque to volume ratio, compact and sturdy design, and enhanced efficiency. It can be difficult to implement various control strategies in various industrial drives, such as flux weakening control and vector control [4] [5].…”
Section: Introductionmentioning
confidence: 99%